Efektivitas Pembelajaran Daring terhadap Prestasi Belajar di SMP Tamansiswa Pematangsiantar - Murniati Murniati (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study aims to determine the effectiveness of online learning at SMP Tamansiswa Pematangsiantar. The implementation of the online model at Tamansiswa Junior High School has online media learning and has the flexibility of time to study. Online learning develops communication between teachers and students in the learning process. Students are also able to manage their time independently and socialize more with their families. Constraints faced in the online learning process include high costs, network, weather, power outages, and internet quotas. In addition, students' learning motivation will decrease if teachers and parents do not carry out intensive learning control. This research is a qualitative field using case study research. Sources of data were taken from the Principal, Deputy Principal, Teachers, Students, and Parents. Data collection techniques include observation, interviews, and documenting.